fIDBAC: A Platform for Fast Bacterial Genome Identification and Typing - Liang, Qian; Liu, Chengzhi; Xu, Rong; Song, Minghui; Zhou, Zhihui; Li, Hong; Dai, Weiyou; Yang, Meicheng; Yu, Yunsong; Chen, Huan (Frontiers in Microbiology, 2021)
To study the contamination of microorganisms in the food industry, pharmaceutical industry, clinical diagnosis or bacterial taxonomy, accurate identification of species is a key starting point of further investigation. The conventional method of Identification by 16S rDNA gene or other marker gene comparison is not accurate, because they used a tiny part of genomic information. The average nucleotide identity calculated between two whole bacterial genomes was proved to be consistent with DNA-DNA hybridization and adopted as the gold standard of bacterial species delineation. Furthermore, more bacterial genomes available in public database recently. All of those contribute to a genome era of bacterial species identification. However, wrong-labeled and low-quality bacterial genome assemblies, especially from type strains, greatly affected the accurate identification. In this study, we employed a multi-step strategy to create a type-strain genome database, by removing the wrong label and low-quality genome assemblies. Based on the curated database, a fast-bacterial genome identification platform (fIDBAC) was developed (http://fbac.dmicrobe.cn/). The fIDBAC is aimed to provide a single, coherent and automated workflow for species identification, strain typing and downstream analysis, such as CDS prediction, drug resistance genes, virulence genes annotation, and phylogenetic analysis.